KEWENANGAN PENGADILAN HUBUNGAN INDUSTRIAL DALAM MENYELESAIKAN PERSELISIHAN PEKERJA - Alandi, Hansen; Ety Mayasari, Dian (Jurnal Hukum Ius Publicum, 2023)
Settlement of problems that occur in Indonesia can be non-litigation or litigation. The process of solving problems through litigation is through the Court. Courts are divided into two, namely general courts and special courts. The Industrial Relations Court is included in the Special Court, which has the authority to resolve Industrial Relations Disputes in accordance with the Industrial Relations Dispute Settlement Act, namely Law Number 2 of 2004. This writing discusses the limits of the authority of the Industrial Relations Court with the existence of SEMA Number 7 of 2012. Types the research used in this paper is normative juridical. The approach used is the statutory approach and the conceptual approach. Analysis using descriptive qualitative. The results of this study note that the settlement of industrial relations disputes through the Industrial Relations Court can be carried out after the non-litigation method of settlement is unsuccessful. Disputes that can be resolved at the Industrial Relations Court are Industrial Relations Disputes, namely Rights Disputes, Interest Disputes, Disputes on Termination of Employment and Disputes Between Labor Unions. The Industrial Relations Court can resolve disputes as long as they are not accompanied by other dispute cases, for example bankruptcy or criminal cases. Keywords: Courts; Disputes; Industrial Relations.